„Suwerenność konsumenta" jako problem teorii i ideologii w rozwoju myśli ekonomicznej - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1981)
A principle of „consumer's sovereignity", understood as production size and structure adjustment to effective demand structure when the share of national income is given under certain market conditions, is a theoretical hypothesis formulated in the seventieth of the 19th century. Free competition is treated by the subjective-marginalistic direction, the trend of which was then originated, as an abstractive model acting in ideal conditions of „perfect competition". Under conditions of „perfect competition" economic equilibrium is shaped automatically by market mechanism as a result of the principle of „consumer's sovereignty", that ensures optimal use of production factors and best satisfaction of needs of individuals and of the whole society. The concept was submitted to the criticism as by bourgeois economy (directly — the theory of imperfect competition, indirectly — the theory of J. Keynes), so by Marxist economy of the twentieth (M. Dobb). A reaction agiainst repeated, expansion of neo-classical economy and formal quantitative theories at the and of sixtieth can be met in case of neo-instátutionalists (J. Galbraith and J. Myrdal), who exaggeratedly negated among others the concept of „homo oeconomicus", the theory of economic equilibrium or the assumption of „consumer's sovereignty". Theoretical hypothesis of „consumer's sovereignty" contains, however, some rational aspects (what was noticed in the interwar period by O. Lange, who formulated a model of socialist economy using regulated market mechanism for rational shaping current economic processes). It should not, however, be treated as the only basis of rational economy also influencing resources allocation and satisfaction of future needs. The principle corresponds then with the purpose of socialist economy (when the share of national income is given and under conditions of consumer's market) provided that individual preferences are not repugnant to social preferences.
"Consumer's Sovereignty" as a Problem of Theory and Ideology i n Development of Economic Thought